(3GdebQHs - (3GHf YUahQ , Ydj Hf eDef Hf eMeO GdMVQej GdGTHjdj, CHh GdMSf,J (B669 (3g` s
(3ChdgG (B:s
(3hHYO aEfg deG cGf Yde GdYQHjI ef CLd GdYdhe bOQkG HGH JHjjf GdcdGe hCLRGFg s
(3BNQgG (B:s
(3hjLhR GdbjGS Ydi eG cKQ ESJYeGdg ef Pdc heGde jcKQ adGSHjd Edi GdbjGS Ydjg hGddg CYde ced GdcJGH HMeO Gddg hYhfg s
(3fSNI NRGFfjIs
(3bQf GdfSN (B:s
(3GdbQf GdSGHYs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B5 - (3U (B27s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3GdfMhs